Pancreatic Enzyme Replacement Therapy Use in Infants With Cystic Fibrosis Diagnosed by Newborn Screening. Issue 4 (April 2018) - Gelfond, Daniel; Heltshe, Sonya L.; Skalland, Michelle; Heubi, James E.; Kloster, Margaret; Leung, Daniel H.; Ramsey, Bonnie W.; Borowitz, Drucy
ABSTRACT: Objectives: The aim of the study is to describe pancreatic enzyme practices during the first year of life in infants with cystic fibrosis (CF) and evaluate associations between dosing and outcomes, including growth and gastrointestinal (GI) symptoms. Methods: We analyzed data from a subset of infants who were in a prospective cohort study conducted at 28 US CF centers. Anthropometric measurements and medications were recorded at each visit. Diaries with infant diet, pancreatic enzyme replacement therapy (PERT) dosing, stool frequency and consistency, and pain were completed by a parent/guardian for 3 days before each visit. Results: Two hundred and thirty-one infants were enrolled in the main study; 205 of these met criteria for pancreatic insufficiency (PI). PERT dose between birth and 6 months was on average 1882 LU/kg per meal (range: 492–3727) and was similar between 6 and 12 months (mean: 1842 LU/kg per mean, range: 313–3612). PERT dose had a weak, negative association with weight z score at 3 and 6 months ( r = −0.16, 95% confidence interval [CI] −0.29 to −0.02 and r = −0.18, 95% CI −0.31 to −0.04, respectively) but not at 12 months. There was not a clear relationship between PERT dosing and number of stools per day, stool consistency or pain. One hundred and forty-four infants (70%) were placed on acid suppression medication. Weight z score mean was 0.37 higher in infants using proton pump inhibitors (PPIs) exclusively versus those using histamine-2 blockers exclusively (95% CI −0.02 to 0.76, P = 0.06). Conclusions: We did not observe that centers with a higher PERT dosing strategy yielded greater clinical benefit than dosing at the lower end of the recommended range. Abstract : Supplemental Digital Content is available in the text